A 'Periodic Table' of mass spectrometry instrumentation and acronyms. Issue 35 (24th August 2017) - Analytical Methods Committee AMCTB No. 81,
Abstract : An overview of mass spectrometry instrumentation is combined with a novel presentation of the techniques and components which aids in decoding their acronyms. Abstract : The development and maturation of mass spectrometry (MS) technology has meant that MS users are no longer required to be experts in this field. With the increasing popularity of mass spectrometry (MS) with non-expert users, the Analytical Methods Committee (AMC) of the Royal Society of Chemistry has highlighted the need to generate a glossary of instrumentation terms that is accessible to users of this technology at all levels. In order to address a wide range of users it is also necessary to provide a context and explanation for the types of MS technology and their acronyms.